Construct validity and reliability of an Adolescent's Coping Strategy instrument - Alif Muarifah; Zhooriyati Zhooriyati; Dian Ari Widyastuti (PSIKOPEDAGOGIA Jurnal Bimbingan dan Konseling, 2021)
The study aims to determine the validity and reliability of the Coping Strategy instrument so that it can be used to explore how adolescents cope with stress in their lives. A total of 100 students of class XI participated in this study. Subjects came from SMA Muhammadiyah 4, SMA Muhammadiyah 5, and SMA Muhammadiyah 6 in the city of Yogyakarta, Indonesia. The sampling technique used to obtain research subjects is stratified sampling. The Coping Strategy instrument proposed in this study is in the form of a scale with a Likert model consisting of 9 items with seven alternative answers. The item arrangement refers to the Coping Strategy aspect, which consists of problem-focused coping and emotion-focused coping. The empirical data that has been collected is then analyzed using the Smart PLS 3.28 program using the Second Order Confirmatory Factor Analysis approach. Based on the results of the analysis, it is known that the aspects and indicators that make up the Coping Strategy construct in this study are declared valid and reliable. The most dominant aspect in reflecting on Coping Strategy is problem-focused coping. The results of the study indicate that the development of the Coping Strategy instrument in adolescents in this study is acceptable because the theory that describes Coping Strategy is in accordance with empirical data obtained from the subject. The results of this study can be used by guidance and counseling teachers or counselors to explore strategies / ways for adolescents to deal with stress using the Coping Strategy instrument.